Do Indonesians Prioritize Sustainability When Giving Their Loyalty to Fast Fashion? - Danu Eko Pranoto; Ananda Sabil Hussein; Nanang Suryadi; Hung-Che Wu (Integrated Journal of Business and Economics (IJBE), 2026)
Fast fashion brands need to increase the need for more ethical alternatives as a substitute for their products that are considered environmentally damaging so that their brand loyalty can increase. Therefore, this study proves the effect of brand love on brand loyalty, with the mediation of customer engagement and moderation of perceived sustainable marketing on the relationship. This study involved 260 respondents obtained through purposive sampling to analyze their answers using the SEM-PLS approach. The results indicate that even though customers already have brand love, it is not enough to make them loyal to the brand. This is because deeper feelings are needed by creating customer engagement first before reaching the loyalty phase. Theoretically, this study confirms that customer engagement plays a full role as a mediator in the relationship between brand love and brand loyalty. Interestingly, it turns out that perceived sustainable marketing does not play a role in moderating the relationship between brand love and brand loyalty. Practically, this study shows that Indonesians don’t really consider sustainability campaigns carried out by fast fashion brands to generate their brand loyalty.